MLXIPL associated with tumor-infiltrating CD8+ T cells is involved in poor prostate cancer prognosis - Fan, Yuanming; Ge, Yuqiu; Niu, Kaiming; Li, Ying; Qi, Lian-Wen; Zhu, Haixia; Ma, Gaoxiang (Frontiers in Immunology, 2024)
Within tumor microenvironment, the presence of preexisting antitumor CD8+ T cells have been shown to be associated with a favorable prognosis in most solid cancers.However, in the case of prostate cancer (PCa), they have been linked to a negative impact on prognosis. To gain a deeper understanding of the contribution of infiltrating CD8+ T cells to poor prognosis in PCa, the infiltration levels of CD8+ T cells were estimated using the TCGA PRAD (The Cancer Genome Atlas Prostate Adenocarcinoma dataset) and MSKCC (Memorial Sloan Kettering Cancer Center) cohorts. Bioinformatic analyses revealed that CD8+ T cells likely influence PCa prognosis through increased expression of immune checkpoint molecules and enhanced recruitment of regulatory T cells. The MLXIPL was identified as the gene expressed in response to CD8+ T cell infiltration and was found to be associated with PCa prognosis. The prognostic role of MLXIPL was examined in two cohorts: TCGA PRAD (p = 2.3E-02) and the MSKCC cohort (p = 1.6E-02). Subsequently, MLXIPL was confirmed to be associated with an unfavorable prognosis in PCa, as evidenced by an independent cohort study (hazard ratio [HR] = 2.57, 95% CI: 1.42-4.65, p = 1.76E-03). In summary, the findings suggested that MLXIPL related to tumor-infiltrating CD8+ T cells facilitated a poor prognosis in PCa.